2022
DOI: 10.1111/tbed.14415
|View full text |Cite
|
Sign up to set email alerts
|

Safety study of Rift Valley Fever human vaccine candidate (DDVax) in mosquitoes

Abstract: Rift Valley fever virus (RVFV) is a mosquito-borne pathogen with significant human and veterinary health consequences that periodically emerges in epizootics. RVFV causes fetal loss and death in ruminants and in humans can lead to liver and renal disease, delayed-onset encephalitis, retinitis, and in some cases severe haemorrhagic fever. A live attenuated vaccine candidate (DDVax), was developed by the deletion of the virulence factors NSs and NSm from a clinical isolate, ZH501, and has proven safe and immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…More recently, a human vaccine candidate for RVFV lacking the NSm gene was unable to infect, replicate, or be transmitted by multiple mosquito species (Campbell et al, 2022 ). Therefore, the NSs and NSm genes appear to be required for the efficient replication of bunyaviruses in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a human vaccine candidate for RVFV lacking the NSm gene was unable to infect, replicate, or be transmitted by multiple mosquito species (Campbell et al, 2022 ). Therefore, the NSs and NSm genes appear to be required for the efficient replication of bunyaviruses in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Drug and Vaccine Development: Artificial feeding methods have emerged as a promising frontier in the development of drugs and vaccines against VBDs. This innovative approach provides a controlled platform for evaluating the efficacy of pharmaceutical compounds and vaccine candidates within a vector–host–pathogen context [ 183 , 184 , 185 ]. Live attenuated vaccine candidates such as DDVax are administered to mosquito vectors using artificial feeding systems, mimicking their natural feeding behaviors [ 185 ].…”
Section: Application Of Artificial Feeding Systemsmentioning
confidence: 99%
“…As part of the safety assessments of DDvax and these other gene deletion RVF viruses, initial mosquito transmission experiments revealed that the NSm gene (and/or P78) confers critical mosquito mid-gut barrier evasion mechanisms that, when deleted, provide an additional environmental containment safety factor. Across several studies, the DDvax research team has definitively demonstrated that DDvax cannot be efficiently transmitted by multiple mosquito vectors due to the specific deletion of the NSm gene region [ 26 , 29 , 64 ]. These results, when taken together, indicated that DDvax might provide in a single dose rapid, safe, and robust protection from RVFV infection with an excellent environmental safety profile that would potentially enable use in both routine and emergency outbreak response-related vaccination campaigns.…”
Section: Current Status Of Next-generation Live-attenuated Rvf Vaccin...mentioning
confidence: 99%